Social provisioning as a starting point for feminist economics - Power, Marilyn (Feminist Economics, 2004)
The past decade has seen a proliferation of writing by feminist economists. Feminist economists are not identified with one particular economic paradigm, yet some common methodological points seem to be emerging. I propose making these starting points more explicit so that they can be examined, critiqued, and built upon. I use the term “social provisioning” to describe this emerging methodology. Its five main components are: incorporation of caring and unpaid labor as fundamental economic activities; use of well-being as a measure of economic success; analysis of economic, political, and social processes and power relations; inclusion of ethical goals and values as an intrinsic part of the analysis; and interrogation of differences by class, race-ethnicity, and other factors. The paper then provides brief illustrations of the use of this methodology in analyses of US welfare reform, gender and development, and feminist ecological economics.
Keywords: OFDIG; approches et analyses; discipline; droits des femmes*; genre; identités LGBTQIA2+; méthodologie; point de vue situé; ressource en ligne; sciences de la gestion; thématiques; économie

Beyond economic man: Feminist theory and economics - Ferber, Marianne A.; Nelson, Julie A. (University of Chicago Press, 1993)
An examination of the central tenets of economics from a feminist point of view. The authors suggest that the discipline of economics could be improved by freeing itself from masculine biases, and raise questions about the discipline's objective nature.
Keywords: OFDIG; approches et analyses; discipline; inégalités; point de vue situé; sciences de la gestion; sexisme; systèmes d'oppressions; thématiques; économie